Effect Pineapple Extract (Ananas comosus L, Merr) To Dadih Quality During Cold Temperature Storage - Benika Naibaho; Rosnawyta Simanjuntak; Samse Pandiangan; Bangun Tampubolon; Riris Siringoringo; Maria Sihotang (Sam Ratulangi University, 2024)
The objectives of this research were to study the effect of storage temperature and pineapple extract on physicochemical, organoleptic, and total bacterial colony of curd. This study used factorial completely randomized design with 2 factors, with two replications. The results showed that storage temperature, pineapple extract and interaction affected significantly fat and protein content, total bacterial colonies, and organoleptis. Storage temperature significantly affected pH, while pineapple extract did not affect pH. The highest fat content wat at room temperature storage without the addition of pineapple extract, namely 12.91%, the highest protein content was at room temperature storage with the addition of 10% pineapple extract, namely 4.74%. Storage at cold temperatures with the addition of 2.5% pineapple extract produced the highest total colonies, namely 2.6 x 106 CFU. At room temperature storage, panelists tended to dislike the color, aroma, and texture of the curd. However, at refrigerator temperature storage, panelists preferred the color of the curd and really liked the taste. Panelists tended to like the curd both without pineapple extract and with pineapple extract. The addition of 7.5% pineapple extract and storage at cold temperatures resulted in a protein content of 4.78% and a fat content of 10.67% which met the National Yoghurt Quality Standard. Keywords: Lactic Acid Bacteria; Curd; Pineapple; Total Bacterial Colonies